Disparities in hospital cost and INA-CBGs tariff with unit cost analysis of inpatient services - Warsi Maryati; Muhammad Faiz Othman; Siti Musyarofah; Puguh Ika Listyorini; Fhahrul Dwi Aryanti; Miftakhul Jannah (Proceeding of International Conference on Science, Health, And Technology, 2021)
The National Health Insurance Program, a form of health insurance that has been implemented since 2014, which uses the Indonesian Case Based Groups (INA-CBGs) system. The implementation of this system ensures that patients get good service and hospitals get standard tariff. The intended tariff is in the form of a package which includes all components of hospital costs. This study aims to determine the relationship between the unit cost of all health service cost components and the INA-CBGs tariff and how the gap is. The research sample was taken from the INA-CBGs claim document in the second quarter of 2020 as many as 4,833. Data were analyzed using linear regression to find a relationship between hospital health service costs and the INA-CBGs tariff. Hospital service costs are calculated based on unit cost analysis. The average unit cost of laboratory was IDR 853,500 (7.91%), radiology IDR 366,198 (3.39%), treatment IDR 2,031,850 (18.82%), Examination IDR 4,205,745 (38.95%), Consumables IDR 345,092 (3.17%), and Drugs IDR 3,022,694 (27.76%). The results of the analysis showed Laboratory (b = 1.639; 95% CI = 1.177 to 2.100; p <0.001), Treatment (b = 0.915; 95% CI = 0.852 to 0.978; p <0.001), Examination and Accommodation (b = 1.211; 95% CI = 1.138 to 1.285; p <0.001), and Drug (b = 0.015; 95% CI = 0.007 to 0.024; p <0.001) had a significant relationship with the INA-CBGs tariff. Other variables such as Radiology (b = -0.141; 95% CI = -0.629 to 0.347; p <0.001) and Consumable Costs (b = -0.343; 95% CI = -696 to 0.009; p <0.001) had no significant relationship with INA-CBGs Tariff. However, all cost components have a significant effect (p <0.001) of 42.7% on the INA-CBG tariff with a strong influence category (R = 0.654). Hospitals must be wiser in managing finances with the INA-CBGs pattern, because the tariff may look small because there are some treatment that are not cost effective or there are still unnecessary treatment for patients taking a large portion of the cost of the package.